2006
DOI: 10.1002/hep.21315
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of integrin-linked kinase in carbon tetrachloride–induced hepatic fibrosis in rats

Abstract: Integrin-linked kinase (ILK) is a multidomain focal adhesion protein implicated in signal transduction between integrins and growth factor receptors. Although its expression is upregulated in pulmonary and renal fibrosis, its role in the development of hepatic fibrosis remains to be determined. Therefore, we considered it important to investigate whether ILK is involved in activation of hepatic stellate cells and thus plays a role in the development of hepatic fibrosis. Immunohistochemical analysis of liver se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 48 publications
4
49
0
Order By: Relevance
“…The mechanism for sensing and transmitting mechanical signals has not been identified in HSC, but, based on data in the literature from other systems, almost certainly involves integrins, their interactions with the cytoskeleton, and downstream signaling networks (3,32). Investigators studying HSC have demonstrated that RGD sequence-mediated interactions, as well as integrin-linked kinase and possibly focal adhesion kinase, are required for HSC differentiation, consistent with the stiffness and matrix dependence we describe (20,34,35,44). Further investigation will be required to determine the role of integrins in HSC mechanotransduction.…”
Section: Discussionsupporting
confidence: 71%
“…The mechanism for sensing and transmitting mechanical signals has not been identified in HSC, but, based on data in the literature from other systems, almost certainly involves integrins, their interactions with the cytoskeleton, and downstream signaling networks (3,32). Investigators studying HSC have demonstrated that RGD sequence-mediated interactions, as well as integrin-linked kinase and possibly focal adhesion kinase, are required for HSC differentiation, consistent with the stiffness and matrix dependence we describe (20,34,35,44). Further investigation will be required to determine the role of integrins in HSC mechanotransduction.…”
Section: Discussionsupporting
confidence: 71%
“…Analysis of canonical ILK-regulated phosphorylation sites, such as Ser473-Akt and Ser9-GSK3β (32,33), demonstrated similar reductions in both ARMS and ERMS cells in response to ILK siRNA (data not shown), which suggests that alternative pathways were involved in the disparate growth effects in ERMS versus ARMS. ILK has previously been demonstrated to indirectly regulate the phosphorylation of members of the MAPK signaling family (14,34,35). Analysis of the phosphorylated MAPKs ERK1 and ERK2 demonstrated similar results to Akt and GSK3β (data not shown).…”
Section: Ilk Induces Opposing Regulation Of the Jnk/c-jun Signaling Amentioning
confidence: 53%
“…Potential mechanosensors such as integrins along with their downstream signaling pathways might be attractive therapeutic targets. 48,49 In summary, we have characterized portal fibroblast activation in vitro and have demonstrated that both TGF-␤ and matrix stiffness are critical for activation to occur. The demonstration that PFs and HSCs are morphologically, geographically, and functionally distinct may have important implications for both the study and treatment of fibrosis.…”
Section: Discussionmentioning
confidence: 95%